2014
DOI: 10.1002/cnm.2667
|View full text |Cite
|
Sign up to set email alerts
|

Calibrating corneal material model parameters using only inflation data: An ill‐posed problem

Abstract: SUMMARYGoldmann applanation tonometry (GAT) is a method used to estimate the intraocular pressure by measuring the indentation resistance of the cornea. A popular approach to investigate the sensitivity of GAT results to material and geometry variations is to perform numerical modelling using the finite element method, for which a calibrated material model is required. These material models are typically calibrated using experimental inflation data by solving an inverse problem. In the inverse problem, the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Therefore, it appears that the mechanical behavior of the matrix will play a significant role in reproducing the corneal response during a tonometry test. Furthermore, some authors have suggested that only one in vivo technique may not be sufficiently accurate for properly characterizing the material properties, such as Kok et al [19,4]. However, at present, it is the only clinical device that permits a non-invasive analysis of the human cornea, as biaxial or inflation tests can only be performed ex vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it appears that the mechanical behavior of the matrix will play a significant role in reproducing the corneal response during a tonometry test. Furthermore, some authors have suggested that only one in vivo technique may not be sufficiently accurate for properly characterizing the material properties, such as Kok et al [19,4]. However, at present, it is the only clinical device that permits a non-invasive analysis of the human cornea, as biaxial or inflation tests can only be performed ex vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The range for the material parameters was determined by considering the experimental results from an inflation test reported in the literature [24,38] and the physiological response of the cornea to an air-puff device (i.e., displacement of the cornea using a CorVis device). First, the inflation tests were used to initially screen the model parameters, to constrain the search space of the optimization and in an attempt to avoid an ill-posed solution [19]. Second, the range of each material parameter was then determined such that the in silico inflation curve was within the experimental window.…”
Section: Introductionmentioning
confidence: 99%
“…To focus on the characterization of the distribution of fibril dispersion κ(ρ, θ), we did not vary other biomechanical parameters and used average values from previous literature. 4 , 31 , 37 The same simplified axially symmetric corneal geometry (0.572-mm central thickness, 0.779-mm peripheral thickness, and 7.97-mm radius of curvature of anterior surface) was used for the three models. 31 The preferential orientations of the collagen fibrils were also assumed to be known and modeled based on previous studies.…”
Section: Methodsmentioning
confidence: 99%
“… 4 Material parameter k 1 and k 2 were set to average values of 91.55 kPa and 785.68, respectively. 37 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation